2021
DOI: 10.3389/fpsyg.2021.730086
|View full text |Cite
|
Sign up to set email alerts
|

Role of Parental Attachment Styles in Moderating Interaction Between Parenting Stress and Perceived Infant Characteristics

Abstract: By employing the transactional model of development and focusing on the multifactorial nature of parenting, this study aimed to (1) examine whether important risk factors, particularly mothers’ insecure attachment styles and parenting stress contribute to the perception of their infants’ characteristics and (2) explore whether maternal attachment styles moderate the relationship between parenting stress and perceived infants’ characteristics. We recruited 357 mothers (age: 34.23; ± 5.38) who had 1-year-old inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Its great innovation is its prospective understanding of development, emphasizing the interaction between various factors underlying different psycho(patho)logies in children ( i.e ., physiological, neuropsychological, cognitive, social, emotional, representational) (Cicchetti & Cohen, 1995 ; Sroufe, 1997 ). Specifically, its childhood assessment considers: i) homotypic and heterotypic continuity ( i.e ., Costello & Angold, 1995 ; Costello et al ., 2003 ) in children’s functioning, to justify early interventions and the monitoring of therapeutic processes and outcomes in light of expected development pathways; ii) the link between early infancy and childhood, especially with regards to cognitive and social functioning and the extent to which these aspects affect children’s functioning during therapeutic treatment; iii) the importance of caregiver-child relationships in predicting problems during development ( i.e ., Sameroff & Emde, 1989 ; Speranza et al ., 2020 ; Quintigliano et al ., 2021 ); and iv) emerging personality patterns ( i.e ., Caspi et al ., 2005 ; Fortunato et al ., 2021 ; Lingiardi et al ., 2010 ; McAdams & Olson 2010 ; Tackett et al ., 2012 ; Widiger et al ., 2009 ), with an understanding that personality falls along a continuum ranging from relatively healthy to more compromised patterns, including conditions that do not reach the threshold for a personality disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Its great innovation is its prospective understanding of development, emphasizing the interaction between various factors underlying different psycho(patho)logies in children ( i.e ., physiological, neuropsychological, cognitive, social, emotional, representational) (Cicchetti & Cohen, 1995 ; Sroufe, 1997 ). Specifically, its childhood assessment considers: i) homotypic and heterotypic continuity ( i.e ., Costello & Angold, 1995 ; Costello et al ., 2003 ) in children’s functioning, to justify early interventions and the monitoring of therapeutic processes and outcomes in light of expected development pathways; ii) the link between early infancy and childhood, especially with regards to cognitive and social functioning and the extent to which these aspects affect children’s functioning during therapeutic treatment; iii) the importance of caregiver-child relationships in predicting problems during development ( i.e ., Sameroff & Emde, 1989 ; Speranza et al ., 2020 ; Quintigliano et al ., 2021 ); and iv) emerging personality patterns ( i.e ., Caspi et al ., 2005 ; Fortunato et al ., 2021 ; Lingiardi et al ., 2010 ; McAdams & Olson 2010 ; Tackett et al ., 2012 ; Widiger et al ., 2009 ), with an understanding that personality falls along a continuum ranging from relatively healthy to more compromised patterns, including conditions that do not reach the threshold for a personality disorder.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, increased parenting stress in the early years can have adverse effects on the parent-child attunement, with cascading effects on the social brain development ( Azhari et al, 2019 ). For example, research on typically developing infants showed that the mother’s perception of infants’ sensory regulatory abilities is influenced by maternal stress linked to parenting ( Quintigliano et al, 2021 ). The current research sustains the importance of early family-centered interventions that support the child development by understanding the parents’ needs and their community ( Dempsey and Keen, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the caregiver-child relationship as a protective or risk factor for development is well-known in the literature ( Cicchetti, 1984 ; Sroufe and Rutter, 1984 ; Emde and Sameroff, 1989 ; Carlson and Sroufe, 1995 ; Emde, 2018 ; Dollberg and Keren, 2020 ; Farina et al, 2020 ; Speranza et al, 2020 ; Quintigliano et al, 2021 ; Yirmiya et al, 2022 ; Quintigliano et al, 2023 ). It is thus essential to consider this relationship when investigating psychopathology continuity.…”
Section: Toward An Understanding Of Continuity: the Role Of Attachmentmentioning
confidence: 99%